Implementation of Qowaid wa Tarjamah Method in Teaching Al-Ajurrumiyyah Nahwu - Nurul Janah; Shodiqul Bahroyni (Journal of Practice Learning and Educational Development, 2026)
This study aims to describe the implementation of the Qowaid wa Tarjamah method in teaching nahwu through Al-Ajurrumiyyah at grades 5 and 6 of Madrasah Diniyah Ula Al Hidayah Karanggupito and to identify the supporting and inhibiting factors affecting its implementation. This study employed a qualitative approach with a descriptive research design. Data were collected through observation, interviews, and documentation. The research participants consisted of the head of the madrasah, the nahwu teacher, and students of grades 5 and 6. Data were analyzed through data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings reveal that the implementation of the Qowaid wa Tarjamah method was carried out through six main stages: introduction, presentation of grammatical rules, text translation, i'rab analysis, memorization, and evaluation. The successful implementation of the method was supported by teacher competence, a strong tradition of kitab kuning learning, students’ learning motivation, institutional support, and the availability of learning resources. Meanwhile, the inhibiting factors included the abstract nature of nahwu materials, limited instructional time, differences in students’ prior abilities, limited learning media, and students’ dual learning burdens. The study concludes that the Qowaid wa Tarjamah method remains relevant for nahwu instruction in madrasah diniyah because it aligns with the objectives of kitab kuning learning and Arabic grammar mastery. However, its implementation requires continuous innovation to meet contemporary educational needs.